Optimization of perfluorosulphonic ionomer amount in gas diffusion electrodes for PEMFC operation under automotive conditions. (20th May 2015) - Gatto, I.; Stassi, A.; Baglio, V.; Carbone, A.; Passalacqua, E.; Aricò, A.S.; Schuster, M.; Bauer, B.
Highlights: Evaluation of the influence of ionomer amount in the catalytic layer as a function of operating conditions. Optimisation of ionomer amount in the catalytic layer as a function of polymer characteristics (hydrophobic/hydrophilic) and operative conditions. An ionomer amount of 50 wt% in the catalytic layer is the best compromise to work at 110 °C low RH and low pressure. ABSTRACT: Perfluorinated sulphonic acid (PFSA) polymers such as Nafion ® are widely used for both electrolyte membrane and ionomer in the catalytic layer because of their high proton conductivity (σH ) as well as chemical and thermal stability. When PFSA polymers alternative to Nafion ® with a different EW are used, it is necessary to optimize the composition of the catalytic ink, considering the different ionomer characteristics. Moreover, fuel cell operating conditions play an important role regarding the catalytic layer optimization. In this work, the influence of ionomer amount in the catalytic layer was evaluated. The electrochemical studies were carried out in a single cell in H2 –O2 at intermediate temperatures (80 °C–130 °C) by using a fumapem ® F-950 membrane as an electrolyte. A hydro-alcoholic dispersion of fumion ® F was also used as an ionomer in the electrode catalytic structure with an amount ranging from 30 to 60%. Under operating conditions finalised to automotive applications (intermediate temperature, low relative humidity and low pressure of gases) an improvement of performance in terms of maximum power density was obtained by using optimized ionomer content.